Enhancing the Performance of Piezoelectric Wind Energy Harvester Using Curve-Shaped Attachments on the Bluff Body - Poudel P.; Sharma S.; Ansari M.N.M.; Vaish R.; Kumar R.; Ibrahim S.M.; Thomas P.; Bowen C. (John Wiley and Sons Inc, 2024)
This paper presents a piezoelectric wind energy harvester that operates by a galloping mechanism with different shaped attachments attached to a bluff body. A comparison is made between harvesters that consist of different shaped attachments on a bluff body